Persistence of IgG Antibody Following Routine Infant Immunization with the 7-Valent Pneumococcal Conjugate Vaccine. Issue 5 (May 2015) - Grant, Lindsay R.; Burbidge, Polly; Haston, Mitch; Johnson, Marina; Reid, Raymond; Santosham, Mathuram; Goldblatt, David; O'Brien, Katherine L.
<x xml:space="preserve">Abstract</x> Background: Pneumococcal conjugate vaccine (PCV) induces protective anticapsular IgG, which mediates disease immunity. IgG persistence may influence long-term protection. Methods: An observational, prospective, longitudinal study of nasopharyngeal carriage among American Indian households from 2006 to 2008 evaluated long-term immunogenicity of 7-valent PCV (PCV7). Children unimmunized with PCV were age-matched to those PCV7 immunized at least 4 years prior (ratio 1:3 or 1:4). Blood collected at the final study visit was analyzed for PCV7 serotype IgG (enzyme-linked immunosorbent assay) and for functional activity (multiplex-opsonophagocytic assay) for serotypes 4, 6B, 14 and 23F. Geometric mean concentrations (GMCs), titers (GMTs) and the odds of serotype-specific IgG ≥0.35 μg/mL were compared according to immunization status using a matched regression approach. Results: Eight unimmunized and 28 immunized children age-matched at the time of serum collection (mean age: 7.9 years) were included. Serotype-specific GMCs, GMTs and proportions above the correlate of protection did not differ between the groups except for serotypes 14 and 23F. Serotype 14 GMCs (immunized 0.7 vs. unimmunized 0.2; P = 0.02) and serotype 23F GMTs (immunized 388.3 vs. unimmunized 47.8; P = 0.03) were significantly higher among immunized children. IgG concentrations and functional titers among immunized children were strongly correlated for serotypes 4 (r = 0.78; P ⩽ 0.001) and 14 (r = 0.52; P ⩽ 0.01). Conclusions: PCV serotype-specific IgG concentrations 4 years following PCV vaccination do not persist above natural levels for most serotypes. Exposure to pneumococcus may be critical in maintaining persistent serotype-specific IgG; the elimination of circulating vaccine type pneumococci by PCV may have effects on long-term immunity.